SNAr nucleophilic substitution of 1, 9-dihalodipyrrins by S- and N- nucleophiles. Synthesis of new dipyrrins bearing pendant substituents. (June 2016) - Leushina, Evgenia; Tikhomirova, Ksenia; Permyakova, Anastasiya; Ilin, Pavel; Terenina, Maria; Anisimov, Alexander; Khoroshutin, Andrey
Abstract: 5-Aryl-1, 9-dichlorodipyrrins react with a series of S- and N- nucleophiles (both alkyl- and aryl- ones). Reagents with mercapto group yield product of double nucleophilic substitution of 5-pheny-1, 9-dichlorodipyrrin, i.e. the respective 1, 9-bis(alkyl-of arylthio)dipyrrin. On the contrary, 5-(4-nitrophenyl)-1, 9-dichlorodipyrrin causes disulfides formation from the S-aliphatic substrates, whereas nucleophilic substitution remains the main path of the reaction for S-aryl ones. The reaction of N-Alkyl nucleophiles proceeds as mono-substitution. UV–Vis spectra feature a batochromic shift for bis-S-substituted products and a hypsochromic shift for mono-N-substituted ones, with respect to the starting dichlrorides. Graphical abstract: Highlights: Free 1, 9-dichlorodipyrrins indergo nucleophilic substitution by S- and N-nucleophiles. S-nucleophiles yield disubstitution, i.e. 1, 9-dithiadipyrrins are the products. N-nucleophiles quantitatively substitute only one chlorine atom. UV–Vis spectra of bis-S-substituted products shift bathochromically as to that of dichlorides. Mono-N-substituted products with H-bonding group feature two bands in the UV–Vis spectra.